Bridging the Gap: Improving Lecturer Adherence to the Tri Dharma of Higher Education through Performance Monitoring - Nurhadi, Ali; Mufarrikoh, Zainatul; Indahsari, Kurniyati; Riskiyah, Eka Maftuhatil; Ifadhah, Hurriyatul (JURNAL AL-TANZIM, 2024)
This research is motivated by the researcher’s interest in the university monitoring system through lecturer performance in improving the quality and reputation of universities in Indonesia. Although the Tri Dharma of Higher Education is an obligation that every lecturer must carry out, there are differences in its implementation in various universities. This study examines the implementation of the Tri Dharma of Higher Education by lecturers and its impact through an independent comparative survey in State Religious Universities and State General Universities with similar geographical, cultural, and social conditions. The approach used in this study is quantitative, with a comparative method to test the differences in the implementation of Tri Dharma in several universities. Data were collected through a validated questionnaire and then analyzed using the Kruskal-Wallis, Mann-Whitney, and Spearman rank correlation tests. The study's results showed no significant differences in the implementation of education and teaching. However, there were differences in the implementation of research and community service among the universities studied. Its impact on the SINTA score shows that the implementation of research has a strong correlation. In contrast, the implementation of community service does not significantly impact the score. This study provides important implications regarding the need for universities to improve the quality of research and community service to impact their academic reputation positively.